La necesidad de implementar tipologías en el nuevo código orgánico integral penal ecuatoriano a fin de garantizar el derecho a la naturaleza, al buen vivir - Abarca Tapia, Roberth Segundo (2015)
The State has the power to sanction illegal behavior different; criminal liability has among its purposes to maintain social order, criminal law is both objective and subjective legal science, the right to punish or impose penalties anti-juridical acts or actions that threaten directly against the rights of the people. It is an exclusive power of the State. The new Code of Criminal Integral legal guarantees to real people from the Constitution of the Republic of Ecuador and the International Instruments, through sanctions that must be typed in order to ensure the rule of law, fundamental rights and guarantees due process. The Ecuadorian State has as one of its objectives the provision of public goods and services, they protect an environment free from all kinds of pollution, hence the need to ensure this right through the prevention and punishment of acts considered harmful or offenses within the new Code of Criminal Integral. Only the State is authorized to establish environmental policies, or preventive mechanisms that fundamental universal principles of criminal law, it is necessary to specifically punish any act or omission that violates the rights of nature and good living. Or SUMAK Kawsay.